Implementing a Marketing Program to Improve Product Knowledge Based on Stimulus–Organism–Response (S-O-R) in the Telecommunications Industry - Muhammad Hafizh Musyaffa Zuhdi; Endy Gunanto Marsasi (Universitas Negeri Padang, 2025)
This study aims to analyze the application of marketing strategies based on the Stimulus–Organism–Response (S-O-R) theory in increasing product knowledge and customer purchasing interest in the telecommunications industry. The research method is a descriptive qualitative approach, incorporating in-depth interviews with account managers and schools as potential customers. The results show that a marketing strategy through a consultative personal selling approach effectively provides comprehensive product education, builds customer trust, and strengthens long-term business relationships. Factors of trust in the manufacturer, information quality, and account manager services have been proven to influence increased product understanding and customer purchasing interest. In addition, partnership programs between educational and industrial actors have also expanded the company's customer reach and strengthened its image as a provider of education-based digital solutions. However, increased advertising creativity and promotional activities are still needed to increase brand awareness of the product. This study confirms that integrating marketing strategies based on the S-O-R theory and increased product knowledge can foster customer loyalty and enhance the company's competitive position in the dynamic telecommunications industry.